2017
DOI: 10.1002/2017tc004540
|View full text |Cite
|
Sign up to set email alerts
|

USArray Imaging of Continental Crust in the Conterminous United States

Abstract: The thickness and bulk composition of continental crust provide important constraints on the evolution and dynamics of continents. Crustal mineralogy and thickness both may influence gravity anomalies, topographic elevation, and lithospheric strength, but prior to the inception of EarthScope's USArray, seismic measurements of crustal thickness and properties useful for inferring lithology are sparse. Here we improve upon a previously published methodology for joint inversion of Bouguer gravity anomalies and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 72 publications
(152 reference statements)
5
47
2
Order By: Relevance
“…Interestingly, our results at depths ≥15 km (i.e., middle and lower crustal depths) beneath the SRM and southern boundaries of the CP do not confirm the values reported in Lowry and Pérez‐Gussinyé () and Ma and Lowry (). At these depths, V p / V s varies between 1.75–1.9, suggesting the presence of either intermediate to mafic lithologies, high temperatures and/or partial melts.…”
Section: Main Results and Discussioncontrasting
confidence: 99%
“…Interestingly, our results at depths ≥15 km (i.e., middle and lower crustal depths) beneath the SRM and southern boundaries of the CP do not confirm the values reported in Lowry and Pérez‐Gussinyé () and Ma and Lowry (). At these depths, V p / V s varies between 1.75–1.9, suggesting the presence of either intermediate to mafic lithologies, high temperatures and/or partial melts.…”
Section: Main Results and Discussioncontrasting
confidence: 99%
“…Other features of the density field estimates can be useful to interpret phase dynamics of the region. Along a profile through the thickest crust in the Illinois basin and the Granite‐Rhyolite province (the Line PP′ in Figure ), we estimate temperatures to be 510 ± 86 °C at 35 km depth and 622 ± 140 °C at 55 km, based on a conductive thermal model combining surface heat flow and mineral physics of Pn seismic velocity (Ma & Lowry, ; Schutt et al, ). Corresponding pressures would be 990 and 1,580 MPa, respectively, assuming 15 km of granitic upper crust (2,750 kg/m 3 ) underlain by gabbro (3,000 kg/m 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…These are supplemented with CRUST1.0 (Laske et al, ) crustal thickness estimates outside the USArray footprint. The seismic imaging does not take into account other crustal and upper mantle interfaces because that requires additional information not included in single‐layer H‐κ receiver function stacks afforded by EARS (e.g., Ma & Lowry, ). Since sedimentary basins could contribute significantly to gravity anomalies, we calculate basin anomalies (Figure ) combining basin thickness estimates from several sources (Ellett & Naylor, ; Hinze et al, ; Laske et al, ; Mooney & Kaban, ) with basin density‐depth variations suggested by Mooney and Kaban ().…”
Section: Methods and Data Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is relatively little change in the observed ratios of La/Yb and Sm/Yb from the observed compositions in the southern Main Ethiopian Rift (Figures 10b and 10c): Gerta Kele (15 Ma;George & Rogers, 2002), Chencha (12 Ma;Rooney, 2010) and Arba Minch (Quaternary; Rooney, 2010). The strong crustal model is capable of matching the observed compositions at Gerta Kele and Chencha (Figures 10b and 10c, stars and triangles), but becomes increasing depleted in the light relative to heavy REEs as the rift evolves.…”
Section: Main Ethiopian Riftmentioning
confidence: 91%